Institutional racism : colonialism, epistemic injustice and cumulative trauma - Ahmed, Shamila (Abingdon, Oxon ; New York, NY : Routledhe, 2024)
"Institutional Racism investigates the factors that created and maintain institutional racism through exploring the role of epistemicide, white frames, and white privilege in sustaining the illusionary status of equality and justice in a perpetrator perspective of institutional racism. The book uses critical race theory, post colonialism and insidious trauma to reveal a victim perspective that documents the cumulative psychological and physical harms of institutional racism. The chapters present an understanding of the factors that created institutional racism through exploring the role of colonialism in creating institutional racism and the construction of truth and knowledge in promoting epistemicide to maintain a perpetrator perspective of institutional racism, demonstration of how epistemicide and colonialism facilitated the existence of white privilege, and white frames to create the mechanisms that sustain institutional racism. The book studies how epistemicide, critical race theory, post colonialism, and insidious trauma can be used to reveal the illusionary status of equality and justice in a perpetrator perspective of institutional racism and move towards a victim perspective of institutional racism that documents the cumulative psychological and physical harms of institutional racism. This book will be of great interest to upper-level students and scholars of criminology, sociology, criminal justice, history, law, and politics, particularly those studying on courses related to race, ethnicity and theory"--
Keywords: Racism; Equality; White privilege (Social structure); SOCIAL SCIENCE / Discrimination & Race Relations; SOCIAL SCIENCE / Minority Studies